From the rhetoric to the real: a critical review of how the concepts of recovery and social inclusion may inform mental health nurse advanced level curricula – the eMenthe project - Stickley, Theodore; Higgins, Agnes; Meade, Oonagh; Sitvast, Jan; Doyle, Luoise; Ellilä, Heikki; Jormfeldt, Henrika; Keogh, Brian; Lahti, Mari; Skärsäter, Ingela; Vuokila-Oikkonen, Paivi; Kilkku, Nina (Elsevier, 2016)
Objectives This critical review addresses the question of how the concepts of recovery and social inclusion may inform mental health nurse education curricula at Master’s level in order to bring about significant and positive change to practice. Design This is a literature-based critical review incorporating a modified rapid review method. It has been said that if done well, this approach can be highly relevant to health care studies and social interventions, and has substantial claims to be as rigorous and enlightening as other, more conventional approaches to literature (Rolfe, 2008). Data sources In this review, we have accessed contemporary literature directly related to the concepts of recovery and social inclusion in mental health. Review methods We have firstly surveyed the international literature directly related to the concepts of recovery and social inclusion in mental health and used the concept of emotional intelligence to help consider educational outcomes in terms of the required knowledge, skills and attitudes needed to promote these values-based approaches in practice. Results A number of themes have been identified that lend themselves to educational application. International frameworks exist that provide some basis for the developments of recovery and social inclusion approaches in mental health practice, however the review identifies specific areas for future development. Conclusions This is the first article that attempts to scope the knowledge, attitudes and skills required to deliver education for Master’s level mental health nurses based upon the principles of recovery and social inclusion. Emotional intelligence theory may help to identify desired outcomes especially in terms of attitudinal development to promote the philosophy of recovery and social inclusive approaches in advanced practice. Whilst recovery is becoming enshrined in policy, there is a need in higher education to ensure that mental health nurse leaders are able to discern the difference between the rhetoric and the reality.